A model of owner estimate cost for software development project in Indonesia. Issue 10 (13th June 2019) - Sholiq; Subriadi, Apol Pribadi; Muqtadiroh, Feby Artwodini; Dewi, Renny Sari
Abstract: The purpose of this study is to develop a model of owner estimate cost of software development projects. The model consists of three main components, namely, personnel direct costs, nonpersonnel direct costs, and taxes. Personnel direct costs are obtained by using the use case points (UCP) method that has been advanced. Initially, UCP was utilized to calculate the effort required to complete the software project. In this study, UCP was institutionalized to obtain personnel direct costs by distributing the acquired effort into each activity in a project. Further, the effort per activity is multiplied by the pay rate for each activity. Personnel direct costs are resulted by adding up the cost of all activities. The experiment has been conducted on nine software development projects in which the model is applied to get the estimated cost calculation.